Analytic calculation of the non-linear cosmic density-fluctuation power spectrum in the Born approximation - Bartelmann, Matthias; Fabis, Felix; Konrad, Sara; Kozlikin, Elena; Lilow, Robert; Littek, Carsten; Dombrowski, Johannes (Arxiv, 2017)
We derive a non-perturbative, closed, analytic equation for the non-linear power spectrum of cosmic density fluctuations. This result is based on our kinetic field theory (KFT) of cosmic structure formation and on evaluating particle interactions in the Born approximation. At redshift zero, relative deviations between our analytic result and typical numerical results are ~ 15 % on average up to wave numbers of k <= 10 h/Mpc. The theory underlying our analytic equation is fully specified once the statistical properties of the initial density and momentum fluctuations are set. It has no further adjustable parameters. Apart from this equation, our main result is that the characteristic non-linear deformations of the power spectrum at late cosmic times are determined by the initial momentum correlations and a partial compensation between diffusion damping and particle interactions.
Identifizierung der Ressource nach: September 2, 2021
Gesehen am 20.05.2022